Gaboriau, Reviewer of the Manners in L’argent Des Autres - Virginie Fernandez (Studia Litterarum)
L’Argent des autres (1873) is not a “true” detective novel like Monsieur Lecoq (1868) written by the same author, Émile Gaboriau. The novel appeared in print eight years after the publication of L’Affaire Lerouge, the first French detective novel; however, there is no police investigation; the culprit is known from the first pages. Like his previous novels, La Dégringolade (1871–1872) and La Corde au cou (1872–1873), L’Argent des autres shows an evolution towards the novel of manners in which Gaboriau reveals the failures of the society of his time. Thus, the novel depicts a dark picture of Parisian finance. Furthermore, if there is a criminal in this serial novel, it is a woman! Gaboriau takes his reader into the viscera of the world of money and discloses the social mechanics of those who live off the money of others. Gaboriau denounces the appetites of the morally corrupt society through the description of fictional spaces, such as the Comptoir de crédit mutuel, the office of the newspaper Le Pilote financier, the office of the speculator Lattermann, on the one hand, and of actual emblematic places such as the Bourse, the large boulevards or the Bois de Boulogne on the other.